(untitled) (International Journal of Food and Nutritional Sciences, 2021)
We analyze the flow of an MHD fluid along a vertical plate, taking into account the Dufour and Soret effects. The ensuing momentum, energy, and concentration equations are rendered similar through standard similarity transformations. These transformed equations are then solved numerically using the fourth-order Runge-Kutta method along with the shooting technique. The impacts of diverse parameters on dimensionless velocity, temperature, and concentration profiles, as well as local values of skin-friction coefficient, Nusselt number, and Sherwood number, are presented through graphical representation and tabulation.